Perancangan Sistem Keamanan Pintar Kamera Night Vision Auto Color berbasis Raspberry PI - Meutia Deli Rachmawati; Abdul Rakhman; Ade Silvia Handayani (Jurnal Qua Teknika, 2021)
In the rapid development of technology, there is a high crime rate. Therefore becomes very important. Many efforts can be made to secure a place and room, such as installing a security lock on the door or using a CCTV camera. But this is not enough to prevent crime from happening. Night Vision is the ability to see either in a biological or technological sense in a dark environment. Night vision capability can be achieved using two approaches, namely increasing the visible spectrum of the wave spectrum or increasing the ability to see low light intensities. Night vision has advantages and disadvantages, especially in conditions of very low light intensity. This technology has developed from time to time such as, there is the camera that uses sophisticated and modern electronic systems. Therefore, in this study, modern technology was designed with a smart security system that can be used to maintain home security or hunt at night.